2018
DOI: 10.1097/sla.0000000000002250
|View full text |Cite
|
Sign up to set email alerts
|

Postoperative Morbidity After Radical Resection of Primary Retroperitoneal Sarcoma

Abstract: A radical surgical approach to RPS is safe when carried out at a specialist sarcoma center. High-risk resections should be carefully considered on an individual basis and weighed against anticipated disease biology. There appears to be no association between surgical morbidity and long-term oncologic outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

14
114
1
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

7
2

Authors

Journals

citations
Cited by 166 publications
(131 citation statements)
references
References 21 publications
14
114
1
2
Order By: Relevance
“…Furthermore, morbidity correlated with specific organ resection; for instance, resection of small bowel, stomach, or major artery was associated with a higher risk of morbidity compared to resection of uterus or psoas muscle . In the large TARPSWG series, overall 30‐day severe morbidity (Clavien‐Dindo ≥ 3) and mortality were 16.4% and 1.8% for patients who underwent resection of primary RPS . The most common complications were bleeding/hematoma (2.9%), bowel anastomotic leak/fistula (2.6%), and abscess (1.7%).…”
Section: Primary Retroperitoneal Sarcomasmentioning
confidence: 99%
“…Furthermore, morbidity correlated with specific organ resection; for instance, resection of small bowel, stomach, or major artery was associated with a higher risk of morbidity compared to resection of uterus or psoas muscle . In the large TARPSWG series, overall 30‐day severe morbidity (Clavien‐Dindo ≥ 3) and mortality were 16.4% and 1.8% for patients who underwent resection of primary RPS . The most common complications were bleeding/hematoma (2.9%), bowel anastomotic leak/fistula (2.6%), and abscess (1.7%).…”
Section: Primary Retroperitoneal Sarcomasmentioning
confidence: 99%
“…This question was investigated by the Transatlantic Retroperitoneal Sarcoma Working Group (TARPSWG), an international collaboration of sarcoma centers. The eight founding centers pooled their contemporary 10‐year data to generate the largest reported experience of RPS resection to date . A total of 1007 patients underwent resection for primary, localized RPS from 2002 to 2011.…”
Section: Extent Of Surgery and Short‐term Morbiditymentioning
confidence: 99%
“…Retrospective studies have shown that this “aggressive” surgical policy is associated with a lower LR incidence and better OS in low‐to‐intermediate grade RPS . Moreover, this approach proved to be safe in terms of short‐ and long‐term morbidity . It is improbable that a randomized‐controlled trial comparing these surgical approaches will be developed.…”
Section: Application Of Nomogram‐based Predictions To the Clinical Prmentioning
confidence: 99%